Pycnogenol® Supplementation Improves Health Risk Factors in Subjects with Metabolic Syndrome. (28th January 2013) - Belcaro, G.; Cornelli, U.; Luzzi, R.; Cesarone; Dugall, M.; Feragalli, B.; Errichi, S.; Ippolito, E.; Grossi, M. G.; Hosoi, M.; Cornelli, M.; Gizzi, G.
<x xml:space="preserve">Abstract</x> This open, controlled study evaluated the effects of 6 month supplementation with Pycnogenol® maritime pine bark extract on health risk factors in subjects with metabolic syndrome. Pycnogenol® was used with the aim of improving risk factors associated with metabolic syndrome, central obesity, elevated triglycerides (TG), low HDL cholesterol, high blood pressure and fasting blood glucose. Sixty‐four subjects (range 45–55 years) presenting with all five risk factors of metabolic syndrome were included, and Pycnogenol® was administered for 6 months. A group of 66 equivalent subjects were followed up as controls. In the 6‐month study Pycnogenol® supplementation 150 mg/day decreased waist circumference, TG levels, blood pressure and increased the HDL cholesterol levels in subjects. Pycnogenol lowered fasting glucose from baseline 123 ± 8.6 mg/dl to 106.4 ± 5.3 after 3 months and to 105.3 ± 2.5 at the end of the study (p < 0.05 vs controls). Men's waist circumference decreased with Pycnogenol from 106.2 ± 2.2 cm to 98.8 ± 2.3 cm and to 98.3 ± 2.1 after 3 and 6 months. Women's waist decreased from 90.9 ± 1.6 cm to 84.6 ± 2.1 cm and to 83.6 ± 2.2 cm after 3 and 6 months. Both genders waist circumference reduction was significant as compared to controls at both time points. In addition, plasma free radicals decrease in the Pycnogenol group was more effective than in the control group (−34.6%; p < 0.05). In conclusion, this study indicates a role for Pycnogenol® for improving health risk factors in subjects with metabolic syndrome. Copyright © 2013 John Wiley & Sons, Ltd.